Effect of three tillage implements on physical properties of an Andisol soil in Tierra Blanca, Cartago - Marín-Araya, Silvia (2023)
Introduction. Implement type and tillage direction in favor of the slope have caused significant soil loss in horticultural soils. This problem has generated a  oss of the most productive horizons and a detriment of the soil´s physical properties. Objective. To determine the effect of the spader plow, rotary plow and rotavator on bulk density, porosity and aggregate stability in an Andisol soil under 2 non-continuous onion cycles in Tierra Blanca, Cartago. Materials and methods. The 3 implements were used in soil preparation for growing onion (Allium cepa L.). Evaluations were carried out on the pre-tillage of the first cycle, at the end of the first cycle, on the pre-tillage of the second cycle and at the end of the second cycle. The evaluated variables were bulk density, porosity and aggregate stability. Results. The soil during the fallow state presented a relatively high bulk density, low porosity and low aggregate stability. With tillage, bulk density decreased, porosity increase and aggregate stability improved during the different evaluation moments. Conclusion. The changes found are a consequence of the soil’s structural reorganization as a product of tillage after a fallow period.